GAMBARAN HARGA, KARAKTERISTIK PRODUK SERTA KEPUTUSAN PEMBELIAN MOBIL TOYOTA INNOVA DI BANDUNG - Safitri, Lusiana; Rahayu, Agus (Journal of Business Management Education (JBME), 2018)
Objective - The purpose of this paper is to determine the effect of price and product characteristics on purchasing decisionsDesign / methodology / approach - This research was conducted in less than 1 year period, so the research design is cross-sectional design. The method used is exolanatory survey, and population 60 respondents. The analysis technique used is descriptive, the questionnaire is used as a research instrument to collect data from respondents.Finding - Based on the results of the study using multiple linear regression analysis, the result that there is a positive influence of price and product characteristics on purchase decision.Originality / value - this study provides a basis for find out the impact of price and product characteristics on purchase decision. The difference of this study with previous research is on the objects, variables, theories and the reference.